Growth by basal branching in two species of Huicungo palms, Astrocaryum carnosum and A. huicungo - Machahua, Miguel (2015)
The basal branching process of Astrocaryum carnosum and A. huicungo is described and its rate and structural expression at the population level is analyzed. Two populations of palms were used in this study, A. carnosum from the Alto Huallaga valley and A. huicungo from the Alto Mayo valley. Branching systems underground were exposed and drawn. For both species, it was established 25 quadrants of 20x20m, in which were counted (i) the number of solitary and caespitose individuals, and (ii) the numbers of axes composing the caespitose individuals. The axes of solitary and caespitose individuals were distributed by growth stages (seedling/juvenile-1/juvenile-2/adult). Seedling and juvenile-1 are not caespitose, basal branching starts in juvenile-2. A. huicungo presents a higher density of axes produced by basal branching than A. carnosum. This branching process in both species by formations of clones from short rhizomes allows an optimized exploitation of space and ensures the continuity of the population over time. However, its role in the spatial propagation of the species is very limited by the shortness of the rhizomes.